Strategi dan Kebijakan Pengembangan Pariwisata Berbasis Kearifan Lokal: Mekanisme Festival Budaya Isen Mulang (FBIM) Menuju Pariwisata Berkelanjutan - Muhammad Zusanri Batubara; M. Syaeful Anam; Atem; Iman Irawansyah (Research and Development Agency Ministry of Home Affairs, 2024)
Strengthening tourism is expected to increase the economy and increase tourist visits. Local wisdom-based tourism development strategies and policies have a significant impact on the sustainability of tourism towards sustainable tourism. This research analyzes the strategies and policies for developing the Isen Mulang Cultural Festival (FBIM) as a local wisdom-based tourist destination, focusing on sustainable tourism. A qualitative research method with a descriptive approach was used to describe the phenomena that occurred, understand the dynamics of festival development in a socio-cultural context, and capture the perspectives of various stakeholders. Data collection techniques included in-depth interviews, direct observation, and document analysis of policies and practices related to the festival, aiming to gain a comprehensive understanding and answers to the research objectives. The results showed that the FBIM development strategy for sustainable tourism was implemented through promotion and collaboration with the private sector. The FBIM’s development policy for sustainable tourism is implemented through the training and empowerment of tourism human resources, local economic empowerment, infrastructure development, and the promotion of local wisdom. The Central Kalimantan Provincial Government has regulated tourism promotion through Regional Regulation Number 3 of 2013 concerning the Tourism Development Master Plan. The FBIM is a featured event in Karisma Event Nusantara 2024, curated by the Ministry of Tourism and Creative Economy. Karisma Event Nusantara 2024 is an event to promote the FBIM to local and foreign tourists so that this festival has sustainability towards sustainable tourism.